IT-gestütztes Compliance Management für Geschäftsprozesse - Karlin, David (KIT Scientific Publishing, 2016)
Compliance with regulatory requirements and internal policies has become increasingly critical to business success. This book presents an approach for efficiently checking the compliance of business processes based on event data recorded in a standardized event log format. In addition to a reference implementation of the approach an extension for a business process management tool as well as a web-based dashboard are developed.